Lijndenia phyllanthifolia (Melastomataceae—Olisbeoideae), new combination for a Critically Endangered shrub of Sri Lanka’s montane forest - Stone, Robert Douglas (Phytotaxa, 2025)
Morphological analysis necessitates the transfer of the Sri Lankan endemic originally described as Memecylon phyllanthifolium to the genus Lijndenia (a group with 17 currently recognized species and a wide overall distribution in the paleotropics). A new combination Lijndenia phyllanthifolia is proposed for this rare and Critically Endangered taxon of montane forest in the Nuwara Eliya and Ratnapura districts.